The clinical and immunological effects of Pru p 3 sublingual immunotherapy on peach and peanut allergy in patients with systemic reactions. Issue 3 (March 2017) - Gomez, F.; Bogas, G.; Gonzalez, M.; Campo, P.; Salas, M.; Diaz‐Perales, A.; Rodriguez, M. J.; Prieto, A.; Barber, D.; Blanca, M.; Torres, M. J.; Mayorga, C.
Summary: Background: The peach non‐specific lipid transfer protein, Pru p 3, is the primary sensitizer in fruits and responsible for severe reactions in the Mediterranean area. Peach allergy is frequently associated with other allergies such as peanut. Therefore, it is important to assess how specific immunotherapy to Pru p 3 could affect both peach and peanut tolerance. Objectives: To evaluate peach and peanut desensitization and immunological changes after 1 year of Pru p 3 sublingual immunotherapy (SLIT) in patients with systemic allergic reactions to peach and/or peanut. Methods: Forty‐eight peach allergic patients, 36 treated with SLIT and 12 non‐treated, were monitored for 12 months. Treated patients were subclassified as peanut allergic (Group A), sensitized (Group B) or tolerant (Group C). SLIT effect was evaluated by skin prick test (SPT) reactivity and food challenge. Immunological changes were evaluated by monitoring sIgE and sIgG4 levels and basophil reactivity. Results: After 1 year of SLIT, the weal area in SPT significantly decreased and a significant increase in peach threshold in treated patients was observed ( P  < 0.001). Patients in Group A showed a significant decrease in peanut SPT weal area and an increase in peanut threshold ( P  < 0.001). Immunological changes were observed in treated patients only, with a significant decrease in sIgE and a parallel increase in sIgG4, sIgG4/sIgE and basophil reactivity for both Pru p 3 and Ara h 9. Conclusions and Clinical Relevance: After 1 year, Pru p 3 SLIT induces both desensitization and immunological changes not only for peach but also for other food allergens relevant in the induction of severe reactions such as peanut.